2011
DOI: 10.1053/j.gastro.2011.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Changes in Diabetic and Idiopathic Gastroparesis

Abstract: Background-Cellular changes associated with diabetic and idiopathic gastroparesis are not well described.Aim-Describe histologic abnormalities in gastroparesis and compare findings in idiopathic versus diabetic gastroparesis.Methods-Full thickness gastric body biopsies were obtained from 40 gastroparetics (20 diabetic) and matched controls. Sections were stained for H&E and trichrome, and immunolabeled with antibodies against PGP 9.5, nNOS, VIP, substance P and tyrosine hydroxylase to quantify nerves, S100β fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
423
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(448 citation statements)
references
References 46 publications
20
423
2
3
Order By: Relevance
“…Considering the low amount of fibrosis reported by other studies such as by Grover et al [10], the authors' findings suggesting a correlation of antral fibrosis and pyloric fibrosis are difficult to interpret given the data of patients with GP where a minority have fibrosis present yet most have symptoms of gastroparesis. Faussone-Pelligrini et al [16] reported ultrastructural differences between idiopathic and diabetic GP with more severe changes present in idiopathic GP.…”
Section: Degree Of Fibrosismentioning
confidence: 66%
See 2 more Smart Citations
“…Considering the low amount of fibrosis reported by other studies such as by Grover et al [10], the authors' findings suggesting a correlation of antral fibrosis and pyloric fibrosis are difficult to interpret given the data of patients with GP where a minority have fibrosis present yet most have symptoms of gastroparesis. Faussone-Pelligrini et al [16] reported ultrastructural differences between idiopathic and diabetic GP with more severe changes present in idiopathic GP.…”
Section: Degree Of Fibrosismentioning
confidence: 66%
“…In a previous study comparing idiopathic-and diabetic-GP patients with healthy controls, surgical biopsy documented loss of ICC in 83% of gastroparesis patients though only 3/40 total GP patients had fibrosis on antral biopsies [10]. Considering the low amount of fibrosis reported by other studies such as by Grover et al [10], the authors' findings suggesting a correlation of antral fibrosis and pyloric fibrosis are difficult to interpret given the data of patients with GP where a minority have fibrosis present yet most have symptoms of gastroparesis.…”
Section: Degree Of Fibrosismentioning
confidence: 88%
See 1 more Smart Citation
“…Several cell types, including the extrinsic innervation to the stomach, enteric nerves, glia, smooth muscle cells, interstitial cell of Cajal (ICC), and immune cells are known to be responsible for normal gastric motility functions. It has been shown that, in diabetic as well as idiopathic patients, the lack of functional coordination between these cell types may have been lost; therefore, the motility of the stomach is impaired and thus leads to abnormal gastric emptying [1].…”
mentioning
confidence: 99%
“…The most common forms include idiopathic, diabetic, and post-surgical complications [1][2][3]. The majority of idiopathic patients are either obese or overweight [3].…”
mentioning
confidence: 99%